2015
DOI: 10.1002/bjs.9766
|View full text |Cite
|
Sign up to set email alerts
|

Global abnormalities in lymphatic function following systemic therapy in patients with breast cancer

Abstract: ISRCTN84866416 ( http://www.isrctn.com).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Adjuvant radiotherapy and systemic therapy have also shown a correlation with the development of BCRL. A few studies have reported an association between BCRL and adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjuvant radiotherapy and systemic therapy have also shown a correlation with the development of BCRL. A few studies have reported an association between BCRL and adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in line with the data reported here and supports a key role of taxanes in the pathogenesis of BCRL. Taxanes may cause systemic disruption, which could have a longer‐term effect on lymphatic function.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also identified polymorphisms in multiple candidate genes that appear to be associated with the development of BCRL [ 36 , 37 ]. Bains et al [ 38 ] also reported abnormal lower limb lymphoscintigraphy in two thirds of the women who had developed upper limb BCRL and in half of the women who had no BCRL, suggesting an unidentified association between breast cancer and lymphatic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one study using near-infrared fluorescent imaging (NIRFLI) found lymphatic architecture abnormalities in both the affected and normal arm in patients with unilateral BCRL, and the percentage of aberrant lymphatics increased with time after initial onset of LE, suggesting that the inflammatory response in LE is systemic. [35][36][37][38][39] Supporting this finding, in a murine model of acute inflammation, systemic lymph propulsive frequency (pumping) and velocity measured using NIRFLI dramatically decreased after a lipopolysaccharide (LPS)-mediated inflammatory insult, before gradually returning to normal values after several days. Changes were not only local, [40][41][42] but systemic (i.e., occurring on both sides of the mouse), despite inflammatory insult on only one side.…”
Section: Systemic Inflammatory Responsementioning
confidence: 96%